Propulsive force asymmetry during tethered-swimming - dos Santos, K. B.; Pereira, G.; Papoti, M.; Bento, P. C. B.; Rodacki, A. (International Journal of Sports Medicine, 2013)
This study aimed to determine whether: i) tethered-swimming can be used to identify the asymmetry during front crawl swimming style; ii) swimmers that perform unilateral breathing present greater asymmetry in comparison to others that use bilateral breathing; iii) swimmers of best performance present smaller asymmetry than their counterparts; iv) repeated front crawl swimming movements influence body asymmetry. 18 swimmers were assessed for propulsive force parameters (peak force, mean force, impulse and rate of force development) during a maximal front crawl tethered-swimming test lasting 2 min. A factorial analysis showed that propulsive forces decreased at the beginning, intermediate and end of the test (p<0.05), but the asymmetries were not changed at different instants of the test. When breathing preference (uni- or bilateral) was analyzed, asymmetry remained unchanged in all force parameters (p>0.05). When performance was considered (below or above mean group time), a larger asymmetry was found in the sub-group of lower performance in comparison to those of best performance (p<0.05). Therefore, the asymmetries of the propulsive forces can be detected using tethered-swimming. The propulsive forces decreased during the test but asymmetries did not change under testing conditions. Although breathing preference did not influence asymmetry, swimmers with best performance were less asymmetric than their counterparts.